Synergistic Interaction of Double/Simple Perovskite Heterostructure for Efficient Hydrogen Evolution Reaction at High Current Density. Issue 2 (8th October 2020) - Liu, Yingying; Dou, Yingnan; Li, Shuang; Xia, Tian; Xie, Ying; Wang, Yan; Zhang, Wei; Wang, Jingping; Huo, Lihuo; Zhao, Hui
Abstract: Electrocatalytic hydrogen production for industrial level requires highly active and cost‐effective catalysts at large current densities. Herein A‐site Ba‐deficient double perovskite PrBa0.94 Co2 O5+ δ (PB0.94 C) is used as a precursor for fabricating PB0.94 C‐based double/simple perovskite heterostructure (PB0.94 C‐DSPH). PB0.94 C‐DSPH with enhanced electrochemical surface area, more hydrophilic surface, and high conductivity ensures abundant active sites, rapid release of gas, and efficient charge transfer at high current densities. The resultant PB0.94 C‐DSPH delivers the overpotential of 364 mV at a current density of 500 mA cm −2 for hydrogen evolution reaction in 1.0 m KOH solution, along with excellent long‐term durability. Promisingly, the electrolyzer with PB0.94 C‐DSPH cathode and NiFe‐layered double hydroxide anode demonstrates high performance for overall water splitting by yielding high current density of 500 mA cm −2 at 1.93 V. Density functional theory calculations indicate that the double/simple perovskite heterostructure promotes the water adsorption, the dissociation of molecular H2 O, and the OH * desorption considerably, which controls the whole hydrogen evolution process. The proposed PB0.94 C‐DSPH solves the problem of low hydrogen‐evolution efficiency at high current density faced by noble metal‐based catalysts in basic environment. This study may provide a route to explore high‐demand elements in the earth for addressing the critical catalysts in clean‐energy utilizations. Abstract : PrBa0.94 Co2 O5+ δ ‐based double/simple perovskite heterostructure (PB0.94 C‐DSPH) is made as excellent electrocatalyst for hydrogen evolution reaction in alkaline media, and it is discovered that the synergistic effect between double/simple perovskites promotes the charge transfer and optimize the free energies of water adsorption/dissociation and OH * desorption, leading to enhanced intrinsic activity for industrial requirement at high current density.